2016
DOI: 10.1371/journal.pone.0158576
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Changes in Cleavage Processing of Amyloid Precursor Protein and Tau following Penetrating Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is an established risk factor for the development of Alzheimer’s disease (AD). Here the effects of severe penetrating TBI on APP and tau cleavage processing were investigated in a rodent model of penetrating ballistic-like brain injury (PBBI). PBBI was induced by stereotactically inserting a perforated steel probe through the right frontal cortex of the anesthetized rat and rapidly inflating/deflating the probe’s elastic tubing into an elliptical shaped balloon to 10% of total rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…In this case, APP is cleaved by β-secretase to release sAPPβ and CTF99, then the γ-secretase complex, cleaves CTF99 to generate Aβ-40/-42 (Cole and Vassar, 2008). Our lab previously indicated that APP loss occurs during subacute PBBI (Cartagena et al, 2016). Therefore, the results presented herein suggest that miRNAs may be coordinated with APP cleavage through enzymes during acute-subacute TBI progression.…”
Section: Pbbi-induced Mirna Dysregulation Is Associated With Bace1 Upmentioning
confidence: 62%
“…In this case, APP is cleaved by β-secretase to release sAPPβ and CTF99, then the γ-secretase complex, cleaves CTF99 to generate Aβ-40/-42 (Cole and Vassar, 2008). Our lab previously indicated that APP loss occurs during subacute PBBI (Cartagena et al, 2016). Therefore, the results presented herein suggest that miRNAs may be coordinated with APP cleavage through enzymes during acute-subacute TBI progression.…”
Section: Pbbi-induced Mirna Dysregulation Is Associated With Bace1 Upmentioning
confidence: 62%
“…APP has been well established as being elevated in the brain acutely after biTBIs, 6 10 as well as blunt force TBIs in preclinical models and penetrating injuries in military personnel. 11 , 12 However, it has been posited that APP plays a neuroprotective role after TBI. 13 Traditionally, the ubiquitously expressed APP has been considered a marker of axonal injury, known to increase after TBI and to relate to the severity of neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Both Aβ40 and Aβ42 were increased at 7 DPI, but the authors explain that detection was difficult due to low expression. Similarly, full length tau decreased at 3 and 7 DPI but oligomeric tau was elevated at 4 h and 7 DPI ( 188 ). Out of these studies, only one reported that increased Aβ and tau pathology occurred in conjunction with neuronal loss and increased MHC-II immunoreactivity several months post-injury ( 177 ).…”
Section: Tbi and Combined Effect Of Amyloid And Tau-related Pathologymentioning
confidence: 99%